The Coverage Rate of Superior Native Chicken Vaccination and Factors Determining Farmers' Decision in the Vaccination Program - I gusti Ayu Putu Mahendri; Ratna Ayu Saptati (Jurnal Ilmu-Ilmu Peternakan, 2023)
The Ministry of Agriculture distributed superior native chicken (KUB) through the BEKERJA program, which was followed by vaccination services as a determinant affecting chicken productivity. This study examined the coverage rate of chicken vaccination and the factors that influence farmers' decision to vaccinate their chickens during the BEKERJA program in Indramayu District, West Java Province. Primary data were collected during vaccination, and secondary data on household characteristics were obtained from the Ministry of Social Affairs. Farmers from 1,549 impoverished households who vaccinated or did not vaccinate their chickens were chosen at random in three sub-districts, and monitoring was done from March to September 2019 during the vaccination program. Descriptive analysis was used to determine farmer characteristics and chicken vaccination coverage rate, while logistic regression analysis was used to determine factors influencing farmers' decision to vaccinate their chickens. The coverage rate of chicken vaccination decreased from 88 percent in the first vaccination period to 63 percent in the sixth vaccination period. Farmers refused vaccination because of previous failures, increasing the mortality rate. Furthermore, the likelihood of implementing a chicken vaccination program was significantly higher for households with a large number of chicken populations, livestock farming experience, and larger land size. However, the number of family members had a smaller effect and respondents' age and residence status did not affect vaccination decisions. As a result, a household's understanding of the importance of vaccination, and the required condition of chickens, must be considered for an effective vaccination strategy.